From Text to Speech: Enhancing EFL Students' Descriptive Speaking Skills through Picture-Guessing Games - Darmadji , Maghfhira Dinda Malindra; Megawati, Fika; Sulikatin, Siti (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
English is a compulsory subject taught at all educational levels in Indonesia. However, many EFL students struggle to achieve fluency in spoken English despite years of study. This disinterest stems from limited enthusiasm and participation. Incorporating innovative media into learning is expected to improve students' speaking skills. Therefore, this research investigates the effect of using pictures in speaking skills development through guessing games. The study employed a quantitative method with a pre-experimental design. A sample of 25 eighth-grade students was selected from a population of 118 at a private school in Sidoarjo. SPSS Version 26 was used to analyze pre- and post-test data. The findings indicate that using pictures in guessing games effectively increased EFL students' speaking abilities, as evidenced by significant score disparities between the pre-test average (11.12) and post-test (16.32). Additionally, the t-count value of 14.066, compared to the t-table value of 2.064 at a 0.05 significance level, suggests a substantial improvement. These results demonstrate that guessing games using pictures significantly enhance student engagement and interest in learning speaking skills. The findings imply that employing pictures in guessing games can potentially enhance student engagement in speaking class activities. Teachers are encouraged to use innovative media to inspire students and enhance their speaking skills.